Diagnóstico de salud bucodental y factores de riesgo en los centros educativos primarios matutinos: Unidad Educativa Mushuc Rimak, escuela luz costa Zabaleta, escuela mariana de Jesus Guanuche, escuela Roberto Andrade, escuela Inka Ñan, escuela Amawta Wasi, escuela monseñor Leonidas Proaño 2, escuela Yachayta Michik, de la Parroquia san Lucas del Cantòn Loja año 2013. - Vélez Macas, Luis Eduardo (2013)
SUMMARY To determine that the oral cavity is one of the parts of our body that need a lot of importance with respect to different oral pathologies , has conducted the present study quantitative, descriptive and transversal , whose aim was to make oral health diagnosis and risk factors in schools : UNIDAD EDUCATIVA MUSHUC RIMAK, ESCUELA LUZ COSTA ZABALETA, ESCUELA MARIANA DE JESUS GUANUCHE, ESCUELA ROBERTO ANDRADE, ESCUELA INKA ÑAN, ESCUELA AMAWTA WASI, ESCUELA MONSEÑOR LEONIDAS PROAÑO 2, ESCUELA YACHAYTA MICHIK Parish in Canton Rural Loja 2013, we worked with 218 students collecting information through surveys and medical records resulting in : Dental Caries 100% , gingival inflammation in 95.41 % , Molar Ratio Distal Step decidua found by 0.91 % , and a plane straight terminal by 0.45 % occlusion types class I Angle keys without crowding by 64.85 %, the risk factors were not brushing 85 , 77 % visit the dentist once a year 65.73 % , consumption of cariogenic food three times a day with 34.4% , plus mild dental fluorosis was found in 22.01% . The prevalence of certain diseases indicates that the study population pays little attention to oral health care , adhering to ignorance of how to keep . Keywords: caries, risk factors, gingival inflammation, malocclusion, dental fluorosis.